IMPROVING INNOVATION AND INVESTMENT CAPACITY MANAGEMENT MECHANISMS IN THE CONSTRUCTION INDUSTRY - Murodjon Goziev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses the implementation and management of innovative and investment processes in the construction industry. Development of projects to increase construction products and introduce them to the market and attract investment flows.